The Icefield Ranges Research Project, 1969 - Ragle, Richard H.; Marcus, Melvin G.; Houston, Charles S. (ARCTIC, 1970)
The Icefield Ranges Research Project (IRRP) - as was visualized nearly ten years ago - becomes each year more and more a complete study of the environment dominated by the St. Elias Mountains, Canada/Alaska. Since 1967, IRRP has been composed of three closely-integrated research units, planned to achieve the proposed aims of IRRP as defined by Dr. W.A. Wood, the original Project Director, accepted by the Arctic Institute's Board of Governors in 1961, and endorsed by the IRRP Advisory Committee. This report reviews the work accomplished by a total of over 65 scientists, their assistants, and support personnel, during the 1969 summer field season, which opened in mid-May and ended the first week in September. It is composed of post-field summaries by principal investigators researching in the disciplines of glaciology, geophysics, physical geography, botany, zoology, archaeology and physiology.